Designer Drugs – “Legal Drugs” – Substances that Threaten Life and Health – the Attitude of Public Administration – Fighting or Controlling? - Stasiak, Jarosław; Matyjek, Sebastian Konrad (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The phenomenon of drug addiction is a global problem, and combating it with traditional methods based on a zero-tolerance policy seems doomed to failure, as exemplified by designer drugs, which were supposed to be legal analogues of conventional drugs. The aim of this study is to try to answer the question of how effective the state has in the fight against new psychoactive substances, commonly known as legal highs. From the content of the work, we learn what legal highs are and how the legislator positions them among other narcotic substances and what methods it uses to fight them. The authors evaluate the effectiveness of the legal solutions ordered by the legislator under private and public law. The result of the above assessment are the postulates of validation ending the work.